METAPHORICAL THINKING LEARNING AND JUNIOR HIGH SCHOOL TEACHERS' MATHEMATICAL QUESTIONING ABILITY - Heris Hendriana; Euis Eti Rohaeti; Wahyu Hidayat (Journal on Mathematics Education, 2017)
This control-group posttest-only experimental design study aims to investigate the role of learning that teaches metaphorical thinking in mathematical questioning ability of junior high school teachers. The population of this study was mathematics junior high school teachers in West Java province. The samples were 82 mathematics junior high school teachers selected using random purposive sampling for experimental class and control class. It was concluded that: 1) the teacher‘s mathematical questioning ability who received metaphorical thinking learning is better than those who received conventional learning; 2) learning factors and KAM (Kemampuan Awal Matematis = Prior Mathematical Ability) affect the achievement of teachers’ mathematical questioning ability; there is an interaction effect between learning and KAM in developing teachers’ mathematical questioning ability; 4) teachers’ mathematical questioning ability does not reach optimal for submitting non-routine and open-ended questions indicator.Keywords: KAM, Mathematical Questioning Ability, Metaphorical Thinking DOI: http://dx.doi.org/10.22342/jme.8.1.3614.55-64